Mycobacterium leprae and host immune transcriptomic signatures for reactional states in leprosy - Das, Madhusmita; David, Diana; Horo, Ilse; Van Hooij, Anouk; Tió-Coma, Maria; Geluk, Annemieke; Vedithi, Sundeep Chaitanya (Frontiers in Microbiology, 2023)
Background: Mycobacterium leprae transcriptomic and human host immune gene expression signatures that demonstrate a plausible association with type I (T1R) and type II reactions (T2R) aid in early diagnosis, prevention of nerve damage and consequent demyelinating neuropathy in leprosy. The aim of the study is to identify M. leprae and host-associated gene-expression signatures that are associated with reactional states in leprosy. Methods: The differentially expressed genes from the whole transcriptome of M. leprae were determined using genome-wide hybridization arrays with RNA extracted from skin biopsies of 20 T1R, 20 T2R and 20 non-reactional controls (NR). Human immune gene expressions were also profiled using RT2- PCR profiler arrays and real-time qPCRs. Results: The RNA quality was optimal in 16 NR, 18 T1R and 19 T2R samples. These samples' whole transcriptome expression array revealed significant upregulation of the genes that encode integral and intrinsic membrane proteins, hydrolases and oxidoreductases. In T1R lesional skin biopsy specimens, the top 10 significantly upregulated genes are ML2064, ML1271, ML1960, ML1220, ML2498, ML1996, ML2388, ML0429, ML2030 and ML0224 in comparison to NR. In T2R, genes ML2498, ML1526, ML0394, ML1960, ML2388, ML0429, ML0281, ML1847, ML1618 and ML1271 were significantly upregulated. We noted ML2664 was significantly upregulated in T1R and repressed in T2R. Conversely, we haven’t noted any genes upregulated in T2R and repressed in T1R. In both T1R and T2R, ML2388 was significantly upregulated. This gene encodes a probable membrane protein, and epitope prediction using Bepipred -2.0 revealed a distinct B-cell epitope. Overexpression of ML2388 was noted consistently across the reaction samples. From the host immune gene expression profiles, CXCL9, CXCL10, CXCL2, CD40LG, IL17A and CXCL11 were upregulated in T1R compared to the NR. In T2R, CXCL10, CXCL11, CXCL9, CXCL2 and CD40LG were upregulated compared to the NR group. Conclusion: A gene set signature involving bacterial genes ML2388, ML2664, and host immune genes CXCL10 and IL-17A can be transcriptomic markers for reactional states in leprosy.